Procedimentos sequenciais Bayesianos aplicados ao processo de captura-recaptura - Santos, Hugo Henrique Kegler dos (2014)
In this work, we make a study of the Bayes sequential decision procedure applied to capture-recapture with fixed sample sizes, to estimate the size of a finite and closed population process. We present the statistical model, review the Bayesian decision theory, presenting the pure decision problem, the statistical decision problem and the sequential decision procedure. We illustrate the theoretical methods discussed using simulated data.